Trace elements in soils and plants - Kabata-Pendias, Alina; Pendias, Henryk (London : CRC Press, 2001)
The Anthroposphere.--Soils and soil processes.--Soil constituents.--Trace elements in plants.--Elements of group I.--Elements of group II.--Elements of group III.--Elements of group IV.--Elements of group V.--Elements of group VI.--Elements of group VII.--Elements of group VIII.
Incluye Apéndice: The following are common plant names used in this book, with corresponding Latin names, and families (in parentheses) to which they are assigned
Incluye Índice
Incluye Bibliografía pag. 331-394)
Keywords: Relación planta -- suelo; Oligoelementos